MicroRNAs Are Key Molecules Involved in the Gene Regulation Network of Colorectal Cancer - Yang, Fangfang; Xuan, Guoyun; Chen, Yixin; Cao, Lichao; Zhao, Min; Wang, Chen; Chen, Erfei (Frontiers in Cell and Developmental Biology, 2022)
Colorectal cancer (CRC) is one of the most common types of cancer and one of the leading causes of mortality worldwide. MicroRNAs (miRNAs) play central roles in normal cell maintenance, development，and other physiological processes. Growing evidence has illustrated that dysregulated miRNAs can participate in the initiation, progression, metastasis, and therapeutic resistance that confer miRNAs to serve as clinical biomarkers and therapeutic targets for CRC. Through binding to the 3'-untranslated region (3'-UTR) of target genes, miRNAs can lead to target mRNA degradation or inhibition at a post-transcriptional level. During the last decade, numerous studies have found numerous miRNAs and their potential targets, but their authentic contribution to CRC initiation and progression remains unknown. In this review, we sought to delineate the complicated roles of the miRNA-target regulation network (Wnt, TGF-β, PI3K-AKT, MAPK and EMT related pathways) in CRC with up-to-date, high-quality data. In particular, we aimed to discuss the downstream miRNAs of certain pathways. We hope that these data can be a robust supplement for the canonical miRNA-target regulation network.